Biochemical aspects of the idiopathic respiratory distress syndrome of the newborn - Hardie, Gwendoline (Division of Chemical Pathology, 2017)
This study was undertaken primarily to investigate the plasma protein system in infants with IRDS, as compared with healthy premature infants, as it had previously been reported that the plasma protein concentration in affected infants was abnormally low. It was attempted further to establish biochemical and/or immunological criteria for diagnosis of the disease and to discover reasons for the low IgG concentrations and raised α-fetoprotein concentrations found in the sera of these infants. Maternal serum proteins were also studied during pregnancy and at and after delivery of the infant. Interrelationships between α-fetoprotein, Human Growth Hormone and other proteins, in immunochemical systems were investigated. In summary, the main conclusions reached were as follows: (i) The total serum-protein concentration in affected infants is much reduced, as compared with healthy premature infants of the same gestational age. (ii) In IRDS infants, the relative and absolute concentration, of IgG is extremely low, whereas concentrations of other immune globulins, as far as could be determined, are within normal limits. (iii) Mothers of affected infants have significantly lower concentrations both of serum IgG and of IgM, than mothers of healthy premature infants. These changes in the serum-proteins are present throughout pregnancy. By six weeks post-partum, the IgG level has returned to normal, but the IgM level remains low. Concentrations of IgA and total serum-protein are normal at all times. (iv) Examination of oedema fluid, urine, faeces and amniotic fluid for γ-globulin content, has excluded the possibility that IgG is being lost from the circulation by these routes. (v) IRDS infants have, in their serum, agglutinins of the IgM type directed against the intact maternal IgG molecule. Similar agglutinins are present in a minority of healthy premature infants. Both IRDS and healthy infants have agglutinins against IgG fragments, in approximately 50% of cases. Agglutinin titres against these are similar in the two groups, but the incidence of agglutinins against Bence Jones protein type Lis raised in IRDS. (vi) Affected infants have an elevated serum concentration of α-fetoprotein, which disappears from the serum during the: first week of post-natal life. (vii) The majority of pregnant women examined have been observed to have serum agglutinins directed against α-fetoprotein. These cross-react with albumin prepared from sera of healthy adult males α-fetoprotein has been found in the serum of many pregnant women, especially during the second trimester. (viii) Immunological interrelationships between α-fetoprotein human serum albumin, Human Growth Hormone and human IgG have been demonstrated. (ix) Infants suffering from Rh-isoimmunization exhibit a serum- protein pattern similar to that seen in IRDS. Biochemical and immunological criteria for the diagnosis of IRDS have thus been established. The data to be presented indicate the presence of an immunological factor in the aetiology of the disease.